Imposing Duties and Taxes in the Context of Imports on Online Personal Shopper Service Providers - Yuliani, Aida Imara (UMPurwokerto Law Review, 2021)
A personal shopper is an effort made by someone on personal social media and has become a trend among the public because of its ease. It is only necessary to hire someone traveling abroad and mention what goods they want will all get in hand without the hassle of going abroad. However, many of these businesses still commit fraud in practice, especially in terms of taxes. They tend to break down goods (splitting during customs checks to avoid taxes and import duties. This study aims to analyze import duties and taxes’ imposition to import online personal shoppers and law enforcement efforts carried out by customs in dealing with personal shoppers who deliberately avoid taxes and import duties. This research uses normative juries research methods through literature by obtaining secondary data in legislation, research results, and scientific journals. Based on the research results, online personal shoppers’ efforts are currently a rampant business in the community.Â This effort gives rise to the act of breaking up luggage or splitting done by an online personal shopper provider. Integrated law enforcement is required by involving relevant agencies and needs special arrangements about online personal shoppers. Keywords: Import duty, taxes, Personal shopper service business. Â